Muscular responses to testosterone replacement vary by administration route: a systematic review and meta‐analysis. Issue 3 (15th March 2018) - Skinner, Jared W.; Otzel, Dana M.; Bowser, Andrew; Nargi, Daniel; Agarwal, Sanjay; Peterson, Mark D.; Zou, Baiming; Borst, Stephen E.; Yarrow, Joshua F.
Abstract: Background: Inconsistent fat‐free mass (FFM) and muscle strength responses have been reported in randomized clinical trials (RCTs) administering testosterone replacement therapy (TRT) to middle‐aged and older men. Our objective was to conduct a meta‐analysis to determine whether TRT improves FFM and muscle strength in middle‐aged and older men and whether the muscular responses vary by TRT administration route. Methods: Systematic literature searches of MEDLINE/PubMed and the Cochrane Library were conducted from inception through 31 March 2017 to identify double‐blind RCTs that compared intramuscular or transdermal TRT vs. placebo and that reported assessments of FFM or upper‐extremity or lower‐extremity strength. Studies were identified, and data were extracted and validated by three investigators, with disagreement resolved by consensus. Using a random effects model, individual effect sizes (ESs) were determined from 31 RCTs reporting FFM (sample size: n = 1213 TRT, n = 1168 placebo) and 17 reporting upper‐extremity or lower‐extremity strength ( n = 2572 TRT, n = 2523 placebo). Heterogeneity was examined, and sensitivity analyses were performed. Results: When administration routes were collectively assessed, TRT was associated with increases in FFM [ES = 1.20 ± 0.15 (95% CI: 0.91, 1.49)], total body strength [ES = 0.90 ± 0.12 (0.67, 1.14)], lower‐extremity strength [ES = 0.77 ± 0.16 (0.45, 1.08)], and upper‐extremity strength [ES = 1.13 ± 0.18 (0.78, 1.47)] ( P < 0.001 for all). When administration routes were evaluated separately, the ES magnitudes were larger and the per cent changes were 3–5 times greater for intramuscular TRT than for transdermal formulations vs. respective placebos, for all outcomes evaluated. Specifically, intramuscular TRT was associated with a 5.7% increase in FFM [ES = 1.49 ± 0.18 (1.13, 1.84)] and 10–13% increases in total body strength [ES = 1.39 ± 0.12 (1.15, 1.63)], lower‐extremity strength [ES = 1.39 ± 0.17 (1.07, 1.72)], and upper‐extremity strength [ES = 1.37 ± 0.17 (1.03, 1.70)] ( P < 0.001 for all). In comparison, transdermal TRT was associated with only a 1.7% increase in FFM [ES = 0.98 ± 0.21 (0.58, 1.39)] and only 2–5% increases in total body [ES = 0.55 ± 0.17 (0.22, 0.88)] and upper‐extremity strength [ES = 0.97 ± 0.24 (0.50, 1.45)] ( P < 0.001). Interestingly, transdermal TRT produced no change in lower‐extremity strength vs. placebo [ES = 0.26 ± 0.23 (−0.19, 0.70), P = 0.26]. Subanalyses of RCTs limiting enrolment to men ≥60 years of age produced similar results. Conclusions: Intramuscular TRT is more effective than transdermal formulations at increasing LBM and improving muscle strength in middle‐aged and older men, particularly in the lower extremities.